Tourism-Energy-Environment-Growth Nexus: Evidence from India - MISHRA, P. K.; ROUT, Himanshu B.; KESTWAL, Ashish K. (Journal of Environmental Management and Tourism; Vol 10 No 5 (2019): JEMT Volume X Issue 5(37) Fall 2019DO - 10.14505//jemt.v10.5(37).25, 2019)
This paper examined the dynamic linkages between tourism development, energy consumption, environmental degradation and economic growth in the context of the Indian economy. The short-run findings establish a chain-link between tourism development, economic growth, energy consumption and environmental degradation. Foreign tourist arrivals positively contribute to economic growth which in turn increases per capita energy use thereby raising CO 2 emissions – a major cause of environmental degradation and consequential adverse effects on tourism development. The long-run findings, although inconclusive, are only indicative of short-run observations. Therefore, the policy focus should be on devising promotional strategies for encouraging the extensive use of clean energy for environmental protection. Such a policy base can be instrumental in fostering the development of India tourism and also, be pivotal for achieving sustainable economic growth.